Multinuclear magnetic resonance characterization and antiproliferative studies of novel dichlorido platinum(II) complexes containing kinetin riboside and 1-β-d-ribofuranosyl-4-(2-pyridyl)-1H-1, 2, 3-triazole. (1st April 2020) - Jakubowski, Mateusz; Łakomska, Iwona; Sitkowski, Jerzy; Pokrywczyńska, Marta; Dąbrowski, Paweł; Framski, Grzegorz; Ostrowski, Tomasz
Graphical abstract: By the reaction between cis -[PtCl2 (dmso)2 ] and kinetin riboside (KR) or 1-β-d -ribofuranosyl-4-(2-pyridyl)-1 H -1, 2, 3-triazole (PTR) in the M:L molar ratio of 1:1, two novel platinum(II) complexes with different compositions of the coordination sphere have been isolated. Biological studies showed that the lipophilic complex cis -[PtCl2 (dmso)(KR)] (2 ) exhibits higher antiproliferative activity towards A549, T24 and CRL1872 cancer cell lines than the complex cis -[PtCl2 (PTR)] (1 ). Highlights: Influence of different binding modes and environment around the platinum(II) on liphophilicity. Role of N -donor ligands in creation of chemotherapeutic prodrugs. Influence of type of riboside on lipophilicity, and in vitro activity. Abstract: The chemical reaction between cis -[PtCl2 (dmso)2 ] and kinetin riboside (KR) or 1-β-d -ribofuranosyl-4-(2-pyridyl)-1 H -1, 2, 3-triazole (PTR) has resulted in two novel platinum(II) complexes being obtained with different compositions of the coordination sphere: cis -[PtCl2 (PTR)] (1 ) and cis -[PtCl2 (dmso)(KR)] (2 ). Based on multinuclear NMR results ( 1 H, 13 C, 15 N, 195 Pt), we have demonstrated that the N -donor ligands PTR and KR are able to coordinate to the Pt(II) ion as bidentate via two nitrogen atoms (N(3) and N(7)) or monodentate via only one nitrogen atom (N(7)), respectively. On the other hand, biological studies showed that the novel platinum(II) complexes exhibit different in vitro cytotoxicity towards A549 (lung carcinoma epithelial cells), T24 (urinary bladder cancer cells) and CRL1872 (malignant melanoma cells). The complex cis -[PtCl2 (dmso)(KR)] (2 ) shows in vitro cytotoxicity against T24 and CRL1872 cell lines (the IC50 parameters amount to 52.2 μM and 21.4 μM, respectively), whereas cis -[PtCl2 (PTR)] (1 ) is not able to inhibit a proliferation of these cells in the range of tested concentrations.